2021
DOI: 10.23846/sr00046
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening intergroup social cohesion in fragile situations

Abstract: Energy and extractives Effects of access to electricity interventions on socio-economic outcomes in low-and middle-income countries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(54 reference statements)
0
2
1
Order By: Relevance
“…Compared to Langer et al (2018) and De Koker et al (2014), we often observe a similar magnitude of small to medium positive effects on empowerment related outcomes although we observe that many of the SRs on similar interventions and outcomes did not report effect sizes but only direction of effect. Conversely, we find the magnitude of effects relatively higher in comparison to the recent 3ie SR on social cohesion (Sonnenfeld et al, 2021), which assessed some similar interventions, but where the largest significant summary effect was 0.10 (SMD), while we find effects as large as 0.87 (SMD).…”
Section: Summary Of Findings and Conclusioncontrasting
confidence: 91%
“…Compared to Langer et al (2018) and De Koker et al (2014), we often observe a similar magnitude of small to medium positive effects on empowerment related outcomes although we observe that many of the SRs on similar interventions and outcomes did not report effect sizes but only direction of effect. Conversely, we find the magnitude of effects relatively higher in comparison to the recent 3ie SR on social cohesion (Sonnenfeld et al, 2021), which assessed some similar interventions, but where the largest significant summary effect was 0.10 (SMD), while we find effects as large as 0.87 (SMD).…”
Section: Summary Of Findings and Conclusioncontrasting
confidence: 91%
“…Life on land The evidence is too weak to draw firm conclusions about the effects of social cohesion interventions in fragile and conflict-affected settings [50].…”
Section: Sdg 15mentioning
confidence: 99%
“…Among the SDG 17 studies that do exist, the only intervention category to evaluated more than once is tax policy, which has been the subject of six evaluations. This suggests that the existing research is related to the first indicator for SDG 17: "Strengthen domestic resource mobilization, including through international support to developing countries, to improve domestic capacity for tax and other revenue collection" [50]. Once eligible studies are identified and added to the portal, 3ie conducts an extensive study coding process to categorise studies and capture additional information that is made available to users of the portal.…”
Section: Sdg 16mentioning
confidence: 99%